Respostas

2013-12-05T12:05:14-02:00
-2x+3               -2x+3                         -2x+3
-2.0+3              -2.(1/3)+3                  -2.(-1/2)+3
0+3                     2/3+3                        2/2+3
=3                      -2+9/3                       2+6/2
                          -2+9/3                        =8/2
                              7/3                         =4
1 5 1
A melhor resposta!
2013-12-05T12:06:29-02:00
- 2x + 3
f(0) = - 2 . 0 + 3
= 0 + 3 
= 3

f(1) = - 2 . 1 + 3 
  3            3
= - 2 + 3
     3
mmc (3) = 3
= - 2 + 9 
       3
= 7/3

f(- 1) = - 2 (- 1) + 3
    2             2
= 2 + 3
   2
= 1 + 3
= 4
2 5 2